The The Influence Of Tax Socialization, The Application Of E-Filing And Tax Sanctions On Individual Taxpayer Compliance - Cecilia L Kewo; Gres Putri Yolanda Sipayung; Miryam P Lonto (ACCOUNTABILITY, 2024)
The study aims to examine the effect of tax socialization, the application of e-filing and tax sanctions on the compliance of individual taxpayers at KP2KP Tondano. Quantitative method was used in this research. The number of samples used was 100 respondents from accidental sampling techniques and data collection was carried out through distributing questionnaires. Data analysis was carried out by multiple linear regression analysis through the help of the SPSS version 26 application. The results prove that the tax socialization, the application of e-filing and tax penalties have a significant effect on individual taxpayer compliance. Partially, tax socialization has a significant and positive effect on individual taxpayer compliance, the application of e-filing has a significant and positive effect on individual taxpayer compliance, while tax sanctions have an insignificant effect on individual taxpayer compliance. Keywords: Taxation, E-Filing, Sanctions, Taxpayer, Compliance